A Rare Case of Duodenal Pseudomelanosis - Marianna D’Ercole; Gianluca Lopez; Luca Elli; Stefano Ferrero; Giorgio Alberto Croci (Diagnostics, 2021)
A black-spotted duodenal mucosa was observed during endoscopy of a man with several comorbidities including hypertension and end-stage kidney disease. Histopathological examination revealed pigment-laden macrophages in the lamina propria of the duodenal villi, which was consistent with duodenal pseudomelanosis.